Technology transfer and research and development (article review) / Juridah Taib - Taib, Juridah (Faculty of Information Management, 2001)
This study is purpose to perform the significance or importance of technology transfer to the public circumstance, to evaluate the revenue of research that related to technology transfer, to find out the successful revenue of R&D in the technology transfer, and to identify the problem and its challenges in the new era circumstance. The methodology that used in this study is library research, which involve gathering the data, or information by surfing the Internet, borrowing some book and also reviewing the articles. The important thing in this study is to know-how the technology transfer work as a developer in the process of R&D. Also to know how far this technology transfer influence to the process of R&D to develop or maintaining in such of process. After made the selected method in this study, there is a finding from the result of the methodology used. From the result that gathered have found that there are many successful stories1 that perform from this technology transfer method, which is used in R&D process. The result also can show the courageous of the technology transfer usage. This will discuss with detail in this study documentation / report.